INNOVATIVE PATHWAYS TO FLUENCY: EXPLORING DUOLINGO WITH SELF-DIRECTED LEARNING - Hamma, Rosmiati; Nur, Rafiah; Ammade, Salasiah; Latifa, Ammang (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
In an increasingly digitalised educational landscape, integrating mobile-assisted language learning (MALL) tools has emerged as a promising strategy to enhance communicative competencies in English, particularly among high school learners. This study explores the effectiveness of the Duolingo application combined with a self-directed learning (SDL) approach in improving English-speaking skills among high school students. Using a quantitative research design, the study was conducted with 57 eleventh-grade students from UPTD SMAN 1 Aralle during the 2024-2025 academic year. Pre-test and post-test assessments measured students' speaking abilities before and after using Duolingo over a designated period. The results revealed a statistically significant improvement, with an average difference of -17.22 between pre-test and post-test scores, supported by a t-value of -8.92 and a significance level of 0.000. This indicates the significant positive impact of Duolingo's interactive features, gamification elements, and self-paced learning model in enhancing students' confidence and competence in speaking English. This research fills a gap in existing studies by focusing on speaking skills and provides practical recommendations for integrating technology into educational practices. It emphasizes the role of teacher guidance, consistent student engagement, and curriculum design to maximize the benefits of technology-driven learning.